Language Strategies in Influencer Content: Building Trust and Buyer Decisions - Siti Afrianty H Kundji; Aryati Hamzah; Fadlia Harun; Mutiara Mahmud (Journal of Governance and Global Studies, 2026)
This study aims to examine how language strategies used by influencers in TikTok live streams can build consumer trust and influence purchasing decisions. The research uses a descriptive qualitative approach, utilizing data obtained through observation and documentation of TikTok live activities used as a product promotion medium. The results show that influencers use various language strategies in the product marketing process, including persuasive language, sharing personal experiences, using social proof, and reducing purchase risk. The persuasive strategy is most often seen in expressions that encourage the audience to buy immediately, such as emphasizing limited-time promotions or product stock availability. In addition, personal experiences shared by influencers and information about high consumer interest in products also help boost potential buyers' trust. This research finding shows that using effective language strategies on TikTok Live can be a means of communication that strengthens consumer trust while also encouraging purchase decisions.